Perkembangan Keterampilan Komunikasi dan Kolaborasi Mahasiswa dalam Pembelajaran Inkuiri Berorientasi Entrepreneurship pada Mata Kuliah Keanekaragaman Tumbuhan - Muhammad Syaipul Hayat; Nuryani Y Rustaman; Adi Rahmat; Sri Redjeki (Universitas Wiralodra, 2019)
The paradigm of learning science, including biology continues to show a fundamental shift. Biology is taught not only through conventional inquiry, but also inquiry that envisions the debriefing of student lifelong learning. One strategy that can build this vision is through entrepreneurship oriented inquiry learning programs. In the mechanism, learning is designed into four stages based on conformity with indicators of entrepreneurship, i.e. stage I (basic), stage II (development), stage III (advance), and stage IV (professional). In the learning experience, students are provided with a variety of skills in a comprehensive manner in accordance with the standards of lifelong learning, among which those that will be studied in this paper are Communication and Collaboration Skills. These two standards become important things to study, because learning biology must not only be scientific but also students must be able to communicate their ideas and be able to build teamwork in solving problems. This research was conducted on the V semester students of the Biology Education Department in one teachers college in Central Java who took part in the course on Plant Diversity. The samples involved in the data collection were 31 people. Data was collected using observation sheets and questionnaires in the form of the Communication & Collaboration rubric adapted from Marzano's framework lifelong learning. There are six items in the rubric that represent data, three of which are about Communication Skills and three about Collaboration. The results of the study showed that on average the Communication Skills of students based on the results of observations had developed at each stage, i.e. stage I (2.45), stage II (2.83), stage III (3.17), and stage IV (3.54). In accordance with the Collaboration data students showed significant developments, i.e. stage I (2.47), stage II (2.89), stage III (3.32), and stage IV (3.60). Based on the results of the questionnaire collected before and after learning, the data showed a significant increase in both communication and collaboration skills. Thus it can be concluded that entrepreneurship-oriented inquiry learning programs applied to plant diversity course can improve student Communication and Collaboration Skills well